Primary dysmenorrhea pain profile among Brazilian women. Case-control study - Flávia Rezende Moura Mesquita Rafael; Natalia Oliveira Bertolini; Samuel Silva; Renato Carvalho Vilella1 (BrJP)
BACKGROUND AND OBJECTIVES: Primary dysmenorrhea (PD) is defined as lower abdominal pain occurring before or during menstruation, unrelated to other diseases. Existing studies investigating potential risk factors for PD development and its incidence in various groups have been fragmented, controversial, or overly broad, posing challenges for analysis. Therefore, this study aims to identify potential risk factors for PD development through a literature-based case-control study. METHODS: Following the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE), this one-year case-control study aimed to establish relationships between PD variables and pain categories (light, moderate, and severe) among 252 Brazilian women. RESULTS: The regularity of the menstrual cycle, intensity of menstrual flow, seeking medical assistance, and use of pain drugs demonstrated statistical significance (p=0.00) across different pain categories. Conversely, factors such as smoking, alcohol consumption, daily diet, physical activity, regular menstrual cycle, previous pregnancy, active sex life, family history of PD, pain site, and the time of onset of PD after the first menstrual cycle were not statistically significant within the pain categories. Although no statistical significance was observed, certain observations can still be drawn by comparing this study with similar ones. CONCLUSION: This study offers valuable insights into the risk factors, pain intensity, menstrual flow patterns, and treatment-seeking behavior associated with PD. By addressing these factors and improving our understanding of PD, we can enhance the well-being and quality of life of women affected by this common gynecological condition.